Simultaneous structuring and scheduling of multiple projects with flexible project structures - Luise-Sophie Hoffmann; Carolin Kellenbrink; Stefan Helber (Journal of Business Economics, 2020)
We study the problem to simultaneously decide on the structures and the schedules for an entire portfolio of flexible projects. The projects are flexible as alternative technologies and procedures can be used to achieve the respective project task. The choice between different technologies and procedures affects the activities to be implemented and thus the precedence relations, i.e., the structure of the project. The different projects have given due dates with specific delay payments and compete for scarce resources. In this situation, project structure decisions and scheduling decisions are highly intertwined and have to be made simultaneously in order to achieve the assumed objective of minimizing the delay payments for the entire project portfolio. The problem is formally stated and solved via novel and problem-specific genetic algorithms. The performance of the new algorithms is evaluated with respect to speed and accuracy in a systematic and comprehensive numerical study.
Keywords: C61; M11; 650; Multi-project scheduling; Flexible projects; Genetic algorithms; RCPSP; RCMPSP